Molecular analysis of coat protein genes of Rice tungro spherical virus from eastern and southern India - INDRANIL DASGUPTA*, VIDHU VERMA and (Indian Phytopathology, 2007)
The nucleotide sequences of the three coat protein (CP) genes- CP1, CP2 and CP3 of Rice tungro spherical virus, member of the two-component tungro virus complex responsible for the rice tungro disease, were determined from diseased rice samples collected from states of Orissa, West Bengal and Tamil Nadu. This is the first report of sequence of three capsid protein genes from India. Analysis of amino acid sequence showed percentage identity of more than 95% to the RTSVCP gene sequences from Philippines and Malaysia. Between them, the three sequences of the Indian isolates showed high identity all along, indicating that the CP genes of RTSV were highly conserved across different geographical regions. In contrast, sequencing of CP gene of one isolate of Rice tungro bacilliform virus, the other member of the virus complex, from the same infected material collected from Orissa showed just 88% identity at the amino acid level to the Philippine isolate. The implications of these findings on our understanding the diversity of RTSVand on efforts to obtain resistance to tungro are discussed.